Efek Pasca Antibiotik Ciprofloxacin terhadap Staphylococcus aureus ATCC 25923 dan Escherichia coli ATCC 25922 - SHIRLY KUMALA; AMEILIA AMEILIA (Fakultas Farmasi Universitas Pancasila, 2009)
Post antibiotic effect is the period required by bacteria to physiologically recover after exposure to antibiotics at certain concentrations and exposure time. This study investigated the post antibiotic effect of ciprofloxacin, one of quinolon derivative with broad spectrum antibiotic activity and highest sensitivity towards both Gram positive and Gram negative bacteria, Staphylococcus aureus ATCC 2593 and Escherichia coli ATCC 25922. Lorian gel membrane filtration technique was used and bacteria were exposed to the antibiotic at a concentration of 10 times of the minimum inhibitionconcentration (MIC) for 2 hours. The findings demonstrated strongly that post-antibiotic effect of the two bacterial strain were different. The Staphylococcus aureus (ATCC 25923) had shorter recovery time Within 2-3 hours When compared to the Escherichia coli (ATCC 25922) which recovered from the post-antibiotic effect Within 3-4 hours.